Taxpayer Compliance In The Perspective Of The Theory Of Planned Behavior With The Intention To Pay Land Tax As A Mediation Variable - Ayu Widuri; Moh. Thamrin; Nursaid Nursaid; Eko Budi Satoto; Nurul Qomariah (UNIVED Press, 2025)
In the state financial structure, taxes occupy a position as the main source of income that has a significant impact on development in Indonesia. This is supported by the fact that more than 70% of total state revenue comes from taxes. This study aims to determine the effect of attitudes, subjective norms, and perceived behavioral control on the intention to pay PBB and taxpayer compliance in Banyuwangi Regency. The population in this study were all Taxpayers in Banyuwangi Regency totaling 822,220 people. The sampling technique used probability sampling, especially simple random sampling and by using the Slovin formula, a sample of 100 respondents was obtained. The data in this study were obtained through a survey method with a questionnaire media. The data analysis technique used partial least square. The results of the study indicate that there is a positive and significant influence of attitude on the intention to pay PBB, there is no positive and significant influence of subjective norms on the intention to pay PBB, there is a positive and significant influence of perceived behavioral control on the intention to pay PBB, attitude has a positive and significant influence on taxpayer compliance, subjective norms have a positive and insignificant influence on taxpayer compliance, perceived behavioral control has a positive and significant influence on taxpayer compliance, intention to pay PBB has a positive and significant influence on taxpayer compliance, intention to pay PBB mediates attitude towards taxpayer compliance, intention to pay PBB does not mediate subjective norms on taxpayer compliance and intention to pay PBB mediates perceived behavioral control on taxpayer compliance. This study is expected to be a recommendation for local governments in improving the achievement of PBB realization.